2020
DOI: 10.1007/s11367-020-01780-2
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the life cycle greenhouse gas balances of microalgae biodiesel

Abstract: Microalgae biodiesel has attracted considerable attention as a potential substitute for fossil fuels and biodiesel from food crops. Nevertheless, its reported climate impacts in the scientific literature vary significantly. This article describes and synthesizes the range of results found in the life cycle assessment (LCA) literature regarding microalgae biodiesel studies to investigate whether particular parameters, e.g. technologies, were associated with higher or lower greenhouse gas (GHG) emissions so that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Examining the life cycle and energy balance of the production of microalgae biomass on a large scale is necessary to analyse the environmental effects of algae-derived biodiesel technology and the profitability of such undertakings [199][200][201]. The life cycle assessment (LCA) of biodiesel made from algae utilising closed and open system cultivations has been the subject of several studies [202][203][204] with Garcia et al [205] conducting a meta-analysis of the life cycle greenhouse gas balances of microalgae biodiesel. Studies on LCA have shown that there is a lot of variation in the technologies taken into account as well as the methodological decisions made, making it impossible to draw reliable conclusions.…”
Section: Sustainability and Life Cycle Assessment In Algae Formentioning
confidence: 99%
See 1 more Smart Citation
“…Examining the life cycle and energy balance of the production of microalgae biomass on a large scale is necessary to analyse the environmental effects of algae-derived biodiesel technology and the profitability of such undertakings [199][200][201]. The life cycle assessment (LCA) of biodiesel made from algae utilising closed and open system cultivations has been the subject of several studies [202][203][204] with Garcia et al [205] conducting a meta-analysis of the life cycle greenhouse gas balances of microalgae biodiesel. Studies on LCA have shown that there is a lot of variation in the technologies taken into account as well as the methodological decisions made, making it impossible to draw reliable conclusions.…”
Section: Sustainability and Life Cycle Assessment In Algae Formentioning
confidence: 99%
“…This may indicate inconsistent findings on biodiesel's effectiveness in comparison to a rival fuel (petroleum diesel) [199]. In some studies, for example, the average GHG emissions reported were more than twice as high as fossil diesel, while some studies showed large benefits [205]. Although several researchers have proposed a framework for the environmental effects of producing algae biodiesel, there is still a great deal of variation in the LCA results due to differences in the life-cycle assessment (LCA) assumptions, life-cycle impact assessment (LCIA) included items, and system boundaries (considered in the LCA) [199].…”
Section: Sustainability and Life Cycle Assessment In Algae Formentioning
confidence: 99%
“…Microalgae biofuel studies were excluded based on the agreement in the most recent reviews, meta-analyses, and harmonized LCA studies that emissions were not reduced consistently compared with fossil fuels [160][161][162] or, on average, even doubled. 163 For each individual combination of CCU technology and type of CO 2 source (fossil, biogenic, or atmospheric), the most recent study with the most complete life cycle inventory was selected. This resulted in 30 studies (1 on direct use, 15 on fuels and chemicals, 8 on mineral carbonates and construction materials, and 6 on EHR), together covering 44 unique CCU technologies and resulting in 74 combinations based on multiple CO 2 sources.…”
Section: Selection Of Lca Studies To Determine the Ghg Intensity Of C...mentioning
confidence: 99%
“…In the pharmaceutical and food industries, a high added value of products entering the market can be often predicted, which opens a wide range of possibilities for microalgae production applications. Lipid production is currently investigated mainly regarding biofuels production, which is, however, still not competitive enough compared to the existing technologies [9,10], even though the algae biodiesel is of comparable quality with other biodiesels [11]. Intensive research on microalgae cultivation, system optimization, and other aspects of the supply chain is currently being carried out using the most advanced algorithms [12].…”
Section: Introductionmentioning
confidence: 99%